Examining the Effect of Haptic Factors for Vascular Palpation Skill Assessment Using an Affordable Simulator - Zhanhe Liu; Joseph Bible; Jared Wells; Deepak Vadivalagan; Ravikiran Singapogu (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: Simulators that incorporate haptic feedback for clinical skills training are increasingly used in medical education. This study addresses the neglected aspect of rendering simulated feedback for vascular palpation skills training by systematically examining the effect of haptic factors on performance. Methods: A simulator-based approach to examine palpation skill is presented. Novice participants with and without minimal previous palpation training performed a palpation task on a simulator that rendered controlled vibratory feedback under various conditions. Results: Five objective metrics were employed to analyze participants’ performance that yielded key findings in quantifying palpation performance. Participants’ palpation accuracy was influenced by all three haptic factors, ranging from moderate to statistically significant. Duration, Total Path Length and Ratio of Correct Movement also demonstrated utility for quantifying performance. Conclusions: We demonstrate that our affordable simulator is capable of rendering controlled haptic feedback suitable for skills training. Further, metrics presented in this study can be used for structured palpation skills assessment and training, potentially improving healthcare delivery.